Performance assessment method for roof-integrated TSSCs. (15th September 2022) - Bushra, Nayab; Hartmann, Timo; Constantin Ungureanu, Lucian
Highlights: A method for integrated and concurrent design of building and TSSCs is introduced. System modeling of TSSC as concentrating thermo-photovoltaic is presented. A parametric modeling approach is used to develop 20, 736 design options. Performance is assessed in terms of av.LMI, covered roof area, and solar cells. Search for the most efficient design options of both roof and TSSCs is enabled. Abstract: This paper proposes a performance assessment method for roof-integrated two-stage solar concentrators (TSSCs) as thermo-photovoltaic systems using a parametric modeling approach. The productivity of TSSCs does not only depend on system design, but also on building geometries ensuring good solar gains. Further, the integration process of TSSCs with buildings is complex and needs to address concerns from multiple domains. The proposed approach intends to be a rigorous yet adaptable method to inform decision making where multiple stakeholders from building and energy domains are involved, and promote the use of TSSCs as sustainable, building-integrated energy production technology. Our method contributes to engineering the TSSC designs in relation to the building design. The method allows generating various design alternatives by controlling a set of input parameters for buildings (i.e., roof type and slope, and building orientation) and TSCCs (i.e., design type, geometric ratio, and separation distance between mirrors). The method applies a parametric modeling approach that enables the generation of 20, 736 design options of building and TSSCs in a collaborative manner, by featuring various combinations of the design inputs. We validated the method in an illustrative case study of a single-family house (California) for a number of performance indicators related to building and TSSCs e.g., the covered roof area, the annual average load match index (av.LMI), and the number of solar cells. We further perform a sensitivity analysis to find the relative importance of design parameters and discuss our results in terms of maximizing av.LMI and minimizing the number of cells and covered roof area. The illustrative application represents that the method enables designers to adopt a performance-based design approach to simultaneously design both; building, and TSSCs that can be integrated with the building, and searches for the most appropriate solutions i.e., building ensuring good solar potential, and TSSC designs offering high av.LMI, covering less building's (roof) area, and utilizing less solar cells. Hence, the method serves as a foundation for future employing generative design approaches for building-integrated TSSCs in the early design stages to support informed decision making processes with a focus on solar integration, and energy planning and transition for self-sufficient and sustainable buildings.